EVALUATION ET IDENTIFICATION D’ACCESSIONS PROMETTEUSES DE MIL [PENNISETUM GLAUCUM (L.) R. BR.,] POUR LEURS APTITUDES GRAINIERE ET FOURRAGERE - Békoye, Béninga Marboua (European Scientific Journal, ESJ, 2015)
Seventy two (72) pearl millet accessions were evaluated for grain and fodder traits. Highly significant differences were observed for all the traits studied while differences for other traits i.e., the width and the length of flag leaf, the weight of the principal spike and the principal spike’s grain weight were non significant. Correlation study between characters revealed that the earing date of the main tiller is negatively correlated with all developmental characters and some production parameters as principal panicle weight, principal spike grain weight and total principal panicle grain weight. Accessions Cem 100, Cem 149 and Cem 243 produced the highest tillers (16,9 ; 16,3 et 15,6 respectively) with small panicles and were promising for high fodder yield. Cem 120, Cem 168, Cem 204, Cem 240 and Cem 244 were promising for high grain yield according to their spike length (35-40 cm) and their 1000 grains weight (12,7 et 14,1 g).